Database and expert systems applications : 13th International Conference, DEXA 2002, Aix-en-Provence, France, September 2-6, 2002 : proceedings - Hameurlain, Abdelkader; Cicchetti, Rosine; Traunmüller, Roland (Lecture Notes in Computer Science, 2002)
th 2002 DEXA, the 13 International Conference on Database and Expert Systems Applications was held on September 2–6, 2002, at the Université Aix–Marseille II, France. The quickly growing field of information systems required the establishment of more specialized discussion platforms (the DaWaK conference, EC-Web conference, eGOV conference and DEXA workshops), and there were held in parallel with DEXA, also in Aix-en-Provence. The resulting book was prepared with great effort. Starting with the preparation of submitted papers, the papers went through the reviewing process. The accepted papers were revised to final versions by their authors and arranged to the conference program. This year 241 papers were submitted and our thanks go to all who have contributed. The program committee and the supporting reviewers produced altogether about 730 referee reports, on average three reports per paper, and selected 89 papers for presentation. The papers presented here encompass the extensive domain of databases; together with the other conferences and workshops of the DEXA event cluster a vast part of applied computer science was covered. In this way DEXA has blazed the trail. At this point we would like to acknowledge to all institutions which actively supported this conference and made it possible. These are: • IUT (Université Aix – Marseille II), • FAW, • DEXA Association, • the Austrian Computer Society, • and Microsoft Research.